2019
DOI: 10.1002/ejhf.1631
|View full text |Cite
|
Sign up to set email alerts
|

Troponins and brain natriuretic peptides for the prediction of cardiotoxicity in cancer patients: a meta‐analysis

Abstract: Aims Cardiac biomarkers are a mainstay in diagnosis of cardiovascular disease but their role in cardio‐oncology has not yet been systematically evaluated. This meta‐analysis aims to determine whether cardiac troponins and (N‐terminal pro) brain natriuretic peptide (BNP/NT‐proBNP) predict cancer therapy‐related left ventricular (LV) dysfunction. Methods and results Scientific databases were searched for studies that assessed troponins or BNP/NT‐proBNP in adult patients undergoing cancer therapy. Data from 61 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
173
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(193 citation statements)
references
References 37 publications
8
173
0
12
Order By: Relevance
“…This threshold level of TnI to detect AIC is in agreement with a previous report by Sawaya et al [20]. A recently published meta-analysis revealed that elevated troponin levels predicted LV dysfunction in patients receiving anthracyclines, but BNP did not [21]. Long-term follow-up data are required to confirm whether elevated BNP is associated with cardiac dysfunction in the chronic phase.…”
Section: Discussionsupporting
confidence: 90%
“…This threshold level of TnI to detect AIC is in agreement with a previous report by Sawaya et al [20]. A recently published meta-analysis revealed that elevated troponin levels predicted LV dysfunction in patients receiving anthracyclines, but BNP did not [21]. Long-term follow-up data are required to confirm whether elevated BNP is associated with cardiac dysfunction in the chronic phase.…”
Section: Discussionsupporting
confidence: 90%
“…Additional to standard LVEF measurements, deformation imaging by means of global longitudinal strain has shown promising results to detect early changes in myocardial contractility in this setting 52 . Other screening methods include biomarkers, of which the most promising is troponin with a negative predictive value of 93% 53 . For primary prevention, ACE-inhibitors and beta-blockers have been studied in breast cancer patients in a small number of trials with limited sample size 54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a meta-analysis including 61 studies and 5691 patients on cancer therapy showed that troponin, but not natriuretic peptide levels, predicts cancer therapyrelated left ventricular dysfunction and that HF therapies decrease troponin levels. 19…”
Section: Cancer Therapies and Heart Failurementioning
confidence: 99%